(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Iron deficiency is a nutritional disorder, it is the most common nutritional disorder worldwide. There are three main stages of reduction of body iron which is a continuous process from iron depletion followed by iron deficiency and then iron deficiency anaemia. Iron is a cation necessary for blood formation. Apart from its role in haemoglobin, it is also needed in various enzyme reactions and cytochromes. It is distributed as an active metabolite and also in storage pools. Iron is an essential component of virtually all living cells, specifically human cells. Iron is an essential micronutrient. it occurs as haem (organic) and non-haem iron (non-organic) in the diet. Maternal supplies are the source of the developing fetus iron stores.